PENGARUH STRES KERJA,KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIBEL INTERVENING PADA ASN DINAS PETERNAKAN DAN PERIKANAN KABUPATEN SITUBONDO - Badriyah, Nuril; Pramesthi, Riska Ayu; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2024)
An agency requires good and appropriate management so that employees can The Livestock and Fisheries Department in Situbondo really need employees who have competence to increase optimal work, utilization of human resources, and contribute to employee performance. The aim of this research is to analyze and examine the influence of work stress, competence and work motivation on performance through job satisfaction. This research refers to a quantitative research. The population of this research was 70 of state civil apparatus at Livestock and Fisheries Department in Situbondo. The sampling technique used saturated sampling. Data analysis and hypothesis test in this research used the Partial Least Square - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application showed that work stress had a positive effect on job satisfaction, work stress had a significant positive effect on performance, competence has a positive but not significant effect on job satisfaction, competence had a significant positive effect on performance, motivation had a significant positive effect on job satisfaction, motivation had a significant positive effect on performance. The results of the indirect effect hypothesis test showed that work stress on performance through job satisfaction had a positive but not significant effect, competence on performance through job satisfaction had a significant positive effect, motivation on performance through job satisfaction had a significantly positive effect.